Newtonian heating effect on Casson fluid flow over nonlinearly stretching sheet - Ahmad, Kartini; Hanouf, Zahir (2016)
The effect of Newtonian heating on Casson fluid flow over a nonlinearly stretching sheet is investigated. By using a suitable similarity transformation, the boundary layer equations, which are given in a set of partial differential equations, are reduced to ordinary differential equations. Those equations are solved numerically using a finite difference technique for some arbitrary values of Casson fluid parameter β, power index of the stretching sheet n, Prandtl number Pr and Biot number γ. It is found that the effects of n, β and γ are to increase both - f "(0)and -(0).